2015
DOI: 10.1515/amm-2015-0081
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Resistance of The Bearing Steel 67SiMnCr6-6-4 with Nanobainitic Structure

Abstract: The paper describes a comparative study of the corrosion resistance of bearing steel 67SiMnCr6-6-4 after two kinds of nanostructuring treatments and two kinds of conventional quenching and tempering treatments. The nanostructuring treatment consisted of austempering with an isothermal quenching at 240• C and 300• C. The conventional heat treatment consisted on quenching and tempering at 350• C for 1 h and quenching and tempering at 550• C for 1 h. Time and temperature of tempering was chosen so that the hardne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…reasons could be that, being highly alloyed materials, they present high resistance and are difficult to process by SPD (in fact, several SPD dies are manufactured with these steels). Some works have studied the grain refinement, and properties of tool steels processed by SPD (14,62,63,64) . The tool steel R6M5 was subjected to severe plastic deformation torsion (SPDT), and the influence of the initial state of the tool surface was studied.…”
Section: Tool Steelsmentioning
confidence: 99%
See 1 more Smart Citation
“…reasons could be that, being highly alloyed materials, they present high resistance and are difficult to process by SPD (in fact, several SPD dies are manufactured with these steels). Some works have studied the grain refinement, and properties of tool steels processed by SPD (14,62,63,64) . The tool steel R6M5 was subjected to severe plastic deformation torsion (SPDT), and the influence of the initial state of the tool surface was studied.…”
Section: Tool Steelsmentioning
confidence: 99%
“…Although there are some works dedicated to study the grain refinement and properties of tool steels processed by SPD (14,62,63,64) , no studies were found for corrosion behavior in these steels. In many applications, tool steels are coated with transition metal carbides to improve corrosion resistance.…”
Section: Tool Steelsmentioning
confidence: 99%
“…A highly refined structure is generally achieved by a low-temperature transformation in the range of 125-350 • C and simultaneously through careful alloy design of high-carbon and high-silicon steels [2]. Typical nanocrystalline high-carbon bainitic steels are characterized by poor overall in-use properties including weldability [3], corrosion resistance [4,5], and limited resistance to tempering processes [6], which are one of the major causes for their restricted industrialization. The concept of enhancing in-use properties by improving the thermal stability of bainitic steels has been extensively described in previous work [7].…”
Section: Introductionmentioning
confidence: 99%
“…24,25 The possibility of generating of ADI cast iron with a nanocrystalline ausferritic matrix was demonstrated for what was said to be the first time. 26,27 The range of research on advanced high strength steels, including nanostructured steels, which encapsulates inter alia their functioning in corrosive environments, 28 where hydrogen embrittlement is an important issue, 29 continues to grow. Another important matter raised at the conference was the practical applications of nanostructured steels 30,31 and cast iron 27 as well as new welding methods [32][33][34] and post-welding treatments to Faculty of Material Science and Engineering, Warsaw University of Technology, ul.…”
mentioning
confidence: 99%
“…The range of research on advanced high strength steels, including nanostructured steels, which encapsulates inter alia their functioning in corrosive environments, 28 where hydrogen embrittlement is an important issue, 29 continues to grow. Another important matter raised at the conference was the practical applications of nanostructured steels 30,31 and cast iron 27 as well as new welding methods 3234 and post-welding treatments to regenerate properties.…”
mentioning
confidence: 99%